First evidence of the Late Pleistocene—Holocene activity of the Roveto Valley Fault (Central Apennines, Italy) - Maceroni, Deborah; Dixit Dominus, Girolamo; Gori, Stefano; Falcucci, Emanuela; Galadini, Fabrizio; Moro, Marco; Saroli, Michele (Frontiers in Earth Science, 2022)
We investigated the late Quaternary activity of a major, crustal fault affecting the southern sector of central Apennines, i.e., the Roveto Valley fault (also known as Liri Valley fault). This sector of the chain was hit by numerous M>5 historical seismic events. For some of these, e.g. the 1654 one (Mw 6.33), the causative seismogenic source has never been conclusively defined. Within this seismotectonic framework, the recent activity of the Roveto Valley fault is still a matter of debate. Some authors defined its activity as ended in the Middle Pleistocene; others considered it as currently active and seismogenic at least in its southern portion. We collected new geologic and geomorphologic data along the eastern (left) flank of the Roveto Valley, where the fault crops out, and we identified evidence of displacement of alluvial fans, that we attributed to the Early, Middle and Late Pleistocene. Moreover, the analysis of the relationship between colluvial/detrital deposits, chronologically constrained by means of radiocarbon dating, allowed us to define activation of the Roveto Valley fault also during historical times, that is, over the past few centuries. Evidence of this has been collected along a large sector of the fault trace, for a length of some tens of kilometres. The results of our studies contribute to improve the knowledge of the seismotectonic setting of a large sector of the central Apennines. Indeed, proving current activity of the Roveto Valley fault casts new light on possible seismogenic sources of major seismicity of central Italy, potentially responsible for severe damage over a wide area and to relevant cities, Rome among them.